Repair of (6‐4) Lesions in DNA by (6‐4) Photolyase: 20 Years of Quest for the Photoreaction Mechanism1. (31st January 2017) - Yamamoto, Junpei; Plaza, Pascal; Brettel, Klaus
Abstract: Exposure of DNA to ultraviolet (UV) light from the Sun or from other sources causes the formation of harmful and carcinogenic crosslinks between adjacent pyrimidine nucleobases, namely cyclobutane pyrimidine dimers and pyrimidine(6–4)pyrimidone photoproducts. Nature has developed unique flavoenzymes, called DNA photolyases, that utilize blue light, that is photons of lower energy than those of the damaging light, to repair these lesions. In this review, we focus on the chemically challenging repair of the (6–4) photoproducts by (6–4) photolyase and describe the major events along the quest for the reaction mechanisms, over the 20 years since the discovery of (6‐4) photolyase. Abstract : Exposure of DNA to ultraviolet light causes formation of harmful and carcinogenic crosslinks between adjacent pyrimidine nucleobases, among them pyrimidine(6–4)pyrimidone photoproducts (T(6‐4)T shown in the figure). Nature has developed a specialized flavoenzyme, (6‐4) photolyase, that utilizes blue light to directly revert (6‐4) lesions to intact nucleobases. The repair reaction is particularly challenging due to the required back transfer of the O4′ atom (in red) and strongly debated since the discovery of (6‐4) photolyase.